The Relationship Between Power of Arm Muscles and Shoulder to the Power of Leg Muscles and the Flexibility of Wrist With the Smash Result on The Pendor Volleyball Team University Of Riau - Vai, Aref; Ramadi, Ramadi; Johanes, Boyke (Proceedings of the UR International Conference on Educational Sciences, 2018)
The purpose of this research was to knowWhether there is a relationship between the power of arm muscles and shoulder with accuracy of Smash onPendor volleyball team University of Riau,?Whether there is a relationship between the Power of leg muscles against accuracy of Smash on Pendor volleyball team University of Riau?, Whether there is a relationship between the flexibility of wrist against the accuracy of Smash on Pendor volleyball team University of Riau?, Whether there is a relationship between the power of arm muscles and shoulder, power of leg and flexibility of wrist against the accuracy of the Smash on Pendor volleyball team University of Riau?,The research was conducted using a correlation research that aims to find out how far the variables on a factor which is related to other factors. The population of research was the son athlete volleyball team Pendor University of riau as many as 16 people, Thevariable research includes free variable consists of an explosive power of leg muscles, arm muscles, flexibility of wrist and variables are bound is the result of smash accuracy.The results of analysing of data obtained calculation of explosive power of leg muscles, strength of arm muscles, flexibility of wrist with normal smash results known F count each of 18.02 (X 1), 34.56 (X 2), and (X 3) 21,88 > F table 4.60 so the hypothesis is accepted. This means that there is a relationship of explosive power of leg muscles, strength of arm muscles, and flexibility of wrist with the results normal smash onpendorVolleyball Team University of Riau.